Peran Media Sosial Sebagai Upaya Pemasaran Bisnis Online Shop Pada Online Shop Antler MakeUp - @antler.makeup - Rusdiono Rusdiono (Universitas Bina Sarana Informatika, 2019)
The purpose of this study was to study the Role of Social Media as an Online Store Business Marketing Effort. This study used a descriptive type of research using qualitative. The research subject is the Online Shop Seller Antler MakeUp which provides information about facts or opinions. @ Antler.makeup on Instagram, @ antler. Make your own selling MakeUp with famous brands not Original but have original grade or really like the original makeup. What attracts the attention of this research is that social media from @antlermakeup is very thematic and neat, this is one of the factors that will influence interested people from online shopping to buy through social media. What's more interesting in Antler MakeUp is always reviewing merchandise in detail in the form of videos or photos on Insta-story, a good form of marketing done by Antler Makeup is to write clearly in the bio description. Viewed from social media @ antler. Using Instagram proved that social media is now very proven in making online shops. However, online social media stores must be very well organized, have an interesting and consistent theme to attract customers to buy goods at online stores. Online business, indeed much easier and cheaper compared to ordinary stores, in terms of business capital, most of the funds can be settled. Keywords: Internet, Social Media, Social Media Marketing, Online Stores,